Profit sharing in Finland: Earnings and productivity effects - Antti Kauhanen; Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2002)
The aim of this paper is to examine profit sharing using Finnish linked employer-employee data in 1996-2000. The use of profit sharing is predicted by the share of the highly educated, R&D and capital intensity, business risk, firm size and the desire to have some stability in the skilled workforce. The probability that an employee is included in a profit sharing plan is higher for educated, R&D employees, white-collar employees and men. Individuals in profit sharing plans have 3-13% higher wages after controlling for the observable characteristics of the employees (3% for white-collar and 13% for blue-collar employees). They also have quicker base wage growth. The productivity effects are 6-13% when the composition of the workforce is controlled for. – – Tässä tutkimuksessa tarkastellaan tulospalkkausta, käyttäen suomalaista yhdistettyä työnantaja-työntekijäaineistoa vuosilta 1996-2000. Tulospalkkauksen käyttöä selittää korkeasti koulutettujen osuus, T&K- ja pääomaintensiivisyys, liikeriski, yrityskoko ja koulutetun työvoiman alhainen vaihtuvuus. Tulospalkkaa saavat todennäköisimmin korkeasti koulutetut, T&K-työntekijät, toimihenkilöt ja miehet. Tulospalkkaa saavilla toimihenkilöillä ansiot ovat noin 3% korkeammat ja työntekijöillä noin 13 % korkeammat, kun havaittavat henkilökohtaiset ominaisuudet on vakioitu. Heidän palkkakasvu on myös ollut nopeampaa. Tuottavuusvaikutukset ovat noin 6-13% kun työvoiman rakenne on otettu huomioon. – palkitsemismenetelmät ; tuottavuus ; palkkaerot ; yhdistetty työnantaja-työntekijäaineisto
Keywords: J32; J33; J53; C23; 330; compensation methods; wage differentials; productivity; linked employeremployee data; Lohndifferenzierung; Produktivität; Tarifliche Gewinnbeteiligung; Finnland